Analysis of the Performance of Islamic Commercial Banks in Indonesia Using the Islamicity Performance Index Approach for the 2014-2016 periods - Sadly, Effendy (International Journal for Educational and Vocational Studies, 2021)
This study aims to reveal the application of Islamic principles to the performance of Islamic Commercial Banks in Indonesia for the 2014 to 2016 period using the Islamicity Performance Index approach. The ratios in the Islamiciti Performance Index are Profit Sharing Ratio, Zakat Performance Ratio, Equitable Distribution Ratio, Directors-employee Wefare Ratio, Islamic Income vs Non-Islamic Income. The data used in this study are secondary data. The population of this research is all Islamic commercial banks in Indonesia from 2014 to 2016 with a sample of two banks, namely Bank Muamalat Indonesia and Bank Syariah Mandiri. Sampling was done using purposive sampling method. The results showed that the performance of Islamic Commercial Banks in Indonesia using the Islamicity Performance Index approach for the period 2014 to 2016 has the predicate "Not Good". There are several unsatisfactory ratios, namely the Zakat Performance ratio, the Equitable Distribution ratio, and the Directors-Employee Ratio. From the results of performance calculations using the Islamicity Performance Index approach among the three banks, namely Bank Muamalat Indonesia, Bank Syariah Mandiri, and Bank BRI Syariah, it shows that the three banks both get the predicate "Good Enough".